2012
DOI: 10.4038/jas.v7i3.4876
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Pheophytin and its Formation as a Chlorophyll Derivative in Selected Crop Species

Abstract: Most

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The chlorophyll degradation mechanisms might occur through the formation of chlorophyllide or pheophytins or both ways if the extract was not exposed to light, heat, and oxygen. In the degradation processes of leaves extract, the main reason for a change in structure from native chlorophyll to pheophytin is that core magnesium ion has lost been in the chlorophyll structure [22].…”
Section: Open Access Receivedmentioning
confidence: 99%
“…The chlorophyll degradation mechanisms might occur through the formation of chlorophyllide or pheophytins or both ways if the extract was not exposed to light, heat, and oxygen. In the degradation processes of leaves extract, the main reason for a change in structure from native chlorophyll to pheophytin is that core magnesium ion has lost been in the chlorophyll structure [22].…”
Section: Open Access Receivedmentioning
confidence: 99%
“…However, in some plants Chlase was found not to be essential for dephytylation. Recent studies have shown that the chlorophyll degradation may progress through the formation of pheophytin a (Pheo a ) as a chlorophyll derivative (Schelbert et al, 2009 ; Dissanayake et al, 2012 ). Based on these findings, it is assumed that Chl degradation pathway is not necessarily via Chlide a but also involves Pheo a .…”
Section: Introductionmentioning
confidence: 99%
“…We cannot exclude the possibility of its artifactual origin due to the extraction procedure. To the best of our knowledge, it has not been recognized before in species belonging to the Plantaginaceae family, being more common to find in algae and crops such as green tea leaves, parsley, bellpepper, and Japanese bunching onion . Compound 1 is known to exert several interesting pharmacological properties such as the antioxidant, antiviral, anti‐inflammatory, antichemotactic, antihepatitis C, and antitumor ones …”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, it has not been recognized before in species belonging to the Plantaginaceae family, being more common to find in algae and crops such as green tea leaves, parsley, bellpepper, and Japanese bunching onion. [16] [17] Compound 1 is known to exert several interesting pharmacological properties such as the antioxidant, antiviral, anti-inflammatory, antichemotactic, antihepatitis C, and antitumor ones. [18 -21] Linariin (2) is a scutellarein derivative which represents a new phytochemical for the species while in the genus its presence has been reported before in K. elatine DUMORT as well as in botanically related entities of the Antirrhinae tribe such as in Linaria aucheri BOISS.…”
Section: Resultsmentioning
confidence: 99%